FREE CONVECTION FLOW OVER A HORIZONTAL POROUS FLAT PLATE WITH THE EFFECT OF MAGNETOHYDRODYNAMICS - Mohammad Ghani (Diponegoro University, 2021)
We are interested in study of the velocity (????′) and temperature (????) profiles for fluid flow over the surface of porous flat plate with the effect of magnetohydrodynamics. The dimensional equations are first transformed into the non-dimensional equations. Then, we transform the non-dimensional equations into the similar equations using stream functions. The numerical results are based on the discretization of similar equations using the finite difference method of Keller-Box. Based on the numerical results, the velocity profiles (????′) decrease when the viscoelastic parameter (????), Prandtl number (????????), magnetic parameter (????), porosity parameter (????) are increased. Moreover, the temperature profile (????) is increased when the viscoelastic parameter (????) and magnetic parameter (????) are increased. However, the temperature profile (????) decreases when Prandtl number (????????) and porosity (????) are increased.